Quick Counting Educational Game for Vocational School Students Based on Scratch (LPPM STMIK Dharmapala Riau, 2023)
Mathematics is a subject that requires thinking to calculate quickly so as not to waste the remaining time studying in class. Educational games are a solution that is offered as a very innovative learning media and can be a learning medium that is fun, fun and addictive. This educational game aims to improve the ability of Vocational High School students to explore and find alternative answers, improve students' ability to make the right decisions and improve students' ability to count. The goal of implementing this program is that high school students still have trouble counting quickly.